PREVALENCE OF CHILDHOOD BRONCHIAL ASTHMA AMONG SCHOOL GOING CHILDREN IN KOMARAPALAYAM, NAMMAKAL DISTRICT,TAMIL NADU,INDIA.: Pharmaceutical Science-Pharmacy - SEN, SNEHA; ELSA VARUGHESE, PRAISY; MOHAMMED ARSHAD K.K; N. VENKATESWARAMURTHY; R. SAMBATHKUMAR (International Journal of Life Science and Pharma Research, 2019)
Childhood asthma is the common chronic illness among school going children. It was a syndrome characterized by airflow obstruction that differs strikingly. There were very few school based studies on the prevalence of asthma in Indian children. We aimed to estimate the prevalence of asthma in children between 12 -15 years of age group at Komarapalayam, Namakkal District, Tamil Nadu on the basis of Intenational Study Of Asthma and Allergies in Childhood (ISAAC) tool. A total of 991 students were selected from three schools of Komarapalayam, Namakkal district for the period of May 2018 to October 2018. The data was collected by using the ISSAC questionnaire. The results obtained were significant for the different age group of students. Out of 991 students, the overall prevalence of childhood asthma was found to be 10.3%. In this study, the total number of diagnosed students was 102 and out of such 102 students, early diagnosed was found to be 48 and newly diagnosed was 54. The higher prevalence was seen in 12 and 15 years of aged category students when compared with the other two. Our study suggested that asthma can be seen more in this study population. So, these exposures can be prevented by giving proper awareness programs for both children and parents, proper education and screening of asthma in school for early diagnosis and better asthma management